1D Seismic Analysis of Earth Dams: The Example of the Lentini Site. (2016) - Castelli, Francesco; Lentini, Valentina; Trifarò, Carla Assunta
Abstract: The assessment of the likely performance of an earth dam during earthquakes is important because its failure can result in significant human and financial losses and severe environmental impact. In the last years the seismic safety assessment of existing dams has evolved itself especially in light of promulgated specific recent laws (D.M. 26 June 2014). On 13th December 1990 the Santa Lucia earthquake caused very strong shaking in many municipalities of oriental Sicily, inducing 17 dead, hundreds injured and thousands homeless. The Lentini earth dam, located in the Val di Noto (South-Eastern Sicily), experienced the earthquake and showed damage and deformation. Damage to embankment dams included cracks in the impervious membrane of asphalt. The aim of this study is to analyze the dynamic response of the earth dam for the input motion of the 1990St. Lucia earthquake and comparing the results of free field 1D PLAXIS simulation to those obtained by the EERA and the MARTA codes, in which the soil is modeled as a linear equivalent material.